Reproductive Performances of Friesian Holstein Dairy Cows in Different Agricultural Ecosystems - Tendy Kusmayadi; Muhamad Hasan Hadiana; Ujang Hidayat Tanuwiria (Buletin Peternakan, 2020)
The objective of this study was to study reproductive performance of Friesian Holstein (FH) dairy cows in the three different agro-ecosystems at the operational area of Bayongbong’s cooperative, Garut regency, Indonesia. The method used in this study was the survey method.  The study was carried out in Lebakjaya village, which has drylands and rainfed agricultural ecosystem (AES DL-Rainfed); Cintanagara village which has drylands and irrigated rice field agricultural ecosystem (AES DL-IRF); and Pamalayan village which has drylands tropical forest (AES DL-Forest). The total samples were 208 dairy farmers and 315 head of FH dairy cows from the three places, 18 dairy farmers and 44 head in Lebakjaya village, 95 dairy farmers and 120 head in Cintanegara village, and 95 dairy farmers with 151 head in Pamalayan village. The study used a simple random sampling and the reproductive performances data were obtained from the field and artificial insemination practices. The data were descriptively analyzed using SPSS 22.0.  After that, it was  tested using  T-Student statistical analyses. The results showed that the reproductive performances in AES DL-Rainfed were S/C 2.23 ± 0.45  times, days open (DO) 148.89 ± 65.52 days, and calving interval (CI) 431.00 ± 65.18 days. The reproductive performances in AES DL-IRF were S/C 2.31 ± 0.54 times, DO 161.95 ± 61.99 days, and CI 444.47 ± 61.21 days, and the reproductive performances in AES DL-Forest were S/C 2.11 ± 0.62 times, DO 138.38 ± 47.18 days, and CI 419.86 ± 46.95 days.  The reproductive performances of AES DL-Forest were more efficient (P<0.05) than the AES DL-IRF. It was concluded that the reproductive performances in the three study locations, for the characters of reproductive value S/C and DO deviated from the ideal estimation, whereas the CI was around the ideal estimation.